Coupling Biocompatible Au Nanoclusters and Cellulose Nanofibrils to Prepare the Antibacterial Nanocomposite Films - Wang, Peng; Yin, Baishuang; Dong, Huiling; Zhang, Yibo; Zhang, Yangheng; Chen, Rixin; Yang, Zukun; Huang, Caoxing; Jiang, Qing (Frontiers in Bioengineering and Biotechnology, 2020)
Cellulose nanofibrils (CNF) is considered as an inexhaustible precursor to produce antibacterial materials, such as antibacterial hydrogel, antibacterial paper, and antibacterial film. However, the poor antimicrobial property of neat CNF required its coupling with an antibacterial ingredient. Herein, biocompatible Au nanoclusters (AuNCs) were synthesized and added into the CNF dispersion to prepare a novel antibacterial film (AuNCs@CNF film). The effects of addition of AuNCs with different amount on the morphology and physicochemical property of AuNCs@CNF films were characterized using atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction (XRD), FTIR (Fourier-transform infrared), light transmittance spectra, and thermogravimetric analysis (TGA). The results showed that the coupled AuNCs did not affect the nanostructural features of the CNF film and its basic structures, but could greatly increase the hydrophilicity, the flexibility, and the thermal stability of the CNF film, which might improve its application in antimicrobial wound-healing dressing. The prepared AuNCs@CNF film demonstrated high antibacterial properties towards Escherichia coli and Streptococcus hemolyticus both in vitro and in vivo, which can prohibit their growth and promote the healing of bacteria-infected wound, respectively. Thus, the AuNCs@CNF film with great antibacterial properties could be applicable in biomedical field.